Lignin modification and saccharification by Pleurotus ostreatus of rice husk (2018)
Semi-solid culture has shown a convenient control of the cultivation as well as high laccase activities. Thus, in this work, P. otreatus was used in biological pre-treatment of rice husk using a semi-solid culture. To reduce the deviation in fungal biomass quantification, it was necessary to establish an inoculum preparation technique. Then, a selectivity to hemicellulose degradation in rice husk was observed in P. ostreatus. A delignification of 9% was achieved in pre-treatment, which increased the rice husk digestibility up to 57%. On the other hand, the aqueous extracts obtained in semi-solid culture showed a dephenolization capacity. Accordingly, this sub-product of pre-treatment is suitable in bioremediation applications. Finally, an inhibition resistance of P. ostreatus was related to higher laccase activity and dephenolization capacity. Then, a limitation in delignification by this fungus was observed. In addition, the delignification process by enzymatic action has not been understood at all. This work, suggests high laccase activity is not necessarily high delignification percentages in pre-treatment.